Relationship of Adjuvant Radiation and the Lymphedema Index: A Valuable Trend to Follow Subclinical Lymphedema in Patients After Immediate Lymphatic Reconstruction. (June 2022) - Wainwright, D'Arcy; Weinstein, Brielle; Tavares, Tina; Panetta, Nicholas J.
Abstract : Background: Immediate lymphaticovenular bypass (immediate lymphatic reconstruction [ILR]) at the time of axillary lymph node dissection has emerged as a preventative paradigm to decrease the incidence of breast cancer–related lymphedema in high-risk patients. These patients are often treated with adjuvant therapies, including radiation. Bioimpedance spectroscopy is a validated tool for trending breast cancer–related lymphedema and identifying subclinical disease. Lymphedema Index (LDEX) values are commonly obtained in ILR patients; however, postoperative trends and relationships with adjuvant treatments are yet to be reported in the literature. Methods: After International Review Board approval, 100 consecutive patients underwent axillary lymph node dissection with axillary reverse lymphatic mapping and ILR at a tertiary cancer center. These patients were then followed prospectively in a multidisciplinary lymphedema clinic at 3-month intervals with clinical examination, circumferential limb girth measurements and bioimpedance spectroscopy (LDEX). Results: Seventy-two patients met inclusion for analysis at 3 months, 60 at 6 months, 51 at 9 months, 45 at 12 months, 41 at 15 months, and 22 at 18 months. A majority of the patients included underwent adjuvant radiation. Average LDEX score for patients who developed lymphedema was 3.02 at 3 months, at 29.1 months, 17.8 at 9 months, 15.05 at 12 months, 18.75 at 15 months, and 7.7 at 18 months. Patients who went on to develop lymphedema had a higher LDEX score at 6 months (29.1 vs 3.20, P = 0.1329), which reached a significant difference beginning at 9 months (17.8 vs 3.19, P = 0.0004). All patients who went on to develop lymphedema received adjuvant radiation. Conclusions: These data provide valuable insight guiding follow-up after ILR. Six-month LDEX is much higher in patients who developed lymphedema, all of which underwent adjuvant radiation therapy, which correlates with the time of completion of their treatment. Average LDEX value after this remains significantly higher in this population. Patients who demonstrate this increase in LDEX and received adjuvant radiation are at highest risk to develop lymphedema despite ILR. All patients who developed lymphedema despite ILR had adjuvant radiation, and this is likely a contributing factor. Injury from adjuvant radiation and its impact after ILR is not insignificant and warrants further studies.